TRANSPARANSI PENDIDIKAN NASIONAL DALAM MENINGKATKAN HASRAT BELAJAR DAN KECERDASAN BANGSA - Washington P. Napitupulu (Perspektif Ilmu Pendidikan, 2007)
National education transparency refers to periodic report that is honest about result reached in every education program. With the existence of the report, public can participate more actively and education program can take place better. The strong learning interest from public needs to be triggered and enhanced and is performed to build and develop learningteaching society. If the transparency has been established, learning interest can be accelerated and the Indonesian people will become smart. Education is carried out by empowering society. Therefore there will be mutual complementary cooperation between government and society.